Analysis of Lattice Temperature Effects on a GaInP/6H-SiC Strained Quantum-Well Lasers - Marjani, Saeid; Faez, Rahim; Ebrahim Hosseini, Seyed (Asian Journal of Chemistry, 2013)
In this paper, simulative study on the effects of lattice temperature on a GaInP/6H-SiC strained quantum-well (QW) laser's device is presented. Loss mechanisms are severe in the edge-emitting lasers. As a consequence, the wall-plug efficiency is sensitive to changes in temperature. The lasers used in this work were separate-confinement quantum-well lasers with a single strained GaInP, located in a lattice-matched waveguide core and cladding region of 6H-SiC. This paper provides the key results of the wall-plug efficiency upon the lattice temperature.